Effectiveness of complex application of organomineral fertilizer EcoFus with the growth regulator Zircon on sage (Salvia officinalis L.) - N. I. Kovalev; E. L. Malankina (Овощи России, 2019)
Relevance. Meeting the needs of the pharmaceutical industry with essential oil raw materials and natural essential oils is relevant.Methods. The aim of the study is to determine the effectiveness the complex application by organomineral fertilizer EcoFys and the growth regulator Zircon on sage (Salvia officinalis L.) in conditions of Non-chernozem zone of the Russian Federation. The experimental part of the work was performed in Institute of Medicinal and Aromatic Plants in 2014-2015 by field experiments.Results. It has been established, that integrated application EcoFys and Zircon can increase yield of culture. In addition, it is shown that contain of essential oil in medicinal raw don’t increase and raising collection of essential oil provides only due to higher yield of herb.